2012
DOI: 10.1172/jci59920
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ceramide antibody prevents the radiation gastrointestinal syndrome in mice

Abstract: Radiation gastrointestinal (GI) syndrome is a major lethal toxicity that may occur after a radiation/nuclear incident. Currently, there are no prophylactic countermeasures against radiation GI syndrome lethality for first responders, military personnel, or remediation workers entering a contaminated area. The pathophysiology of this syndrome requires depletion of stem cell clonogens (SCCs) within the crypts of Lieberkühn, which are a subset of cells necessary for postinjury regeneration of gut epithelium. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 27 publications
7
110
0
Order By: Relevance
“…Pertinent to this, ceramides were linked to the pathogenesis of NAFLD through insulin resistance, oxidative stress, and inflammation (65,66). Numerous reports have indicated that ceramide levels were positively associated with the degree of hepatic triglyceride content accumulation (67,68). However, the precise mechanism by which intestinal FXR regulates ceramide synthesis metabolism remains unclear and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pertinent to this, ceramides were linked to the pathogenesis of NAFLD through insulin resistance, oxidative stress, and inflammation (65,66). Numerous reports have indicated that ceramide levels were positively associated with the degree of hepatic triglyceride content accumulation (67,68). However, the precise mechanism by which intestinal FXR regulates ceramide synthesis metabolism remains unclear and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of DAGs and ceramides is associated with cellular and tissue dysfunction including defective insulin signaling (23), increased apoptosis (24), and activation of protein kinases (25). To test whether the lipid abnormalities observed in severe human heart failure were due to changes in DGAT1 expression, we deleted Dgat1 in cardiomyocytes; these mice are denoted hDgat1 Ϫ/Ϫ .…”
mentioning
confidence: 99%
“…Previously, it was shown in an in vitro model for tissue fixed macrophages that exposure of cultured THP-1 cells to endotoxin resulted in PKCζ mediated activation of SMPD1, ceramide generation as well as assembly of TLR4 receptors within lipid rafts which was attenuated by functional inhibition with imipramine (16,53). A clearly protective role of inhibition of macrodomain formation was recently shown in irradiation-induced mortality (54). Otherwise, non-lysosomal sphingomyelinase can protect against cytotoxic agents (55).…”
Section: Acknowledgmentsmentioning
confidence: 99%